Layers of time: An investigation of transformation by adaptive reuse - Lidström, Klara (My University, 2023)
Dating back as early as during the French revolution, and probably before that, until today’s expansion of our societies, the question of reuse within architecture has been widely discussed and become more and more of a prominent topic. As a sustainable approach intending to extend the life of old buildings and work as an economically beneficial strategy on how to further develop our cities, adaptive reuse is an architectural theory that’s been evolving for centuries characterized by it’s many different theories and approaches. However, with an expanding building stock consisting of unused buildings of different typologies and historical identities, the question of how these approaches might be developed and used within modern society is something that is still to be further explored. This thesis aims to investigate one possible approach within this field by researching the strategies of palimpsest, translatio, imtatio and aemulatio and their effect upon a building of cultural and historical heritage. The building that will be investigated is M-verkstaden, a former industrial building residing in Kvarteret Gösen in Gamlestaden, a place of great historical importance for the development of the area. Starting out in 1907 when Svenska Kullagerfabriken, SKF, started their production in the neighborhood, until today, Kvarteret Gösen is considered a landmark in Gamlestaden. But with the relocation of SKF the area is today facing a transition from a closed industrial neighborhood into a future public place, something that brings the topic of adaptive reuse into question and how the identity of this place will be translated. By documenting M-verkstaden as a palimpsest and then applying the strategies of translatio, imitatio and aemulatio onto the research the intention is to give a possible answer to this question while also adding to the discussion of what adaptive reuse might be and how it can be further developed.
Keywords: Adaptive; Reuse; Heritage; Palimpsest